The Effectiveness of Bank BTN’s Youtube Ads Against Purchasing Decisions - Farhan Alfarel; Noor Aziz; Baroya Mila Shanty (Universitas Muhammadiyah Malang, 2021)
Bank BTN has always been nominated for a top of top brand awards from 2016 to 2019. This phenomenon shows the brand image of Bank BTN, which has long been known as an icon of the bank with the best homeownership credit products as a positive value that can influence purchasing decisions. The purpose of this study was to determine whether the Bank BTN’s Youtube ads were effective. The dimensions of the Bank BTN YouTube ads included empathy, persuasion, impact, and communication on the BTN bank Youtube ads. The variables used in this study include empathy, persuasion, impact, communication, advertising effectiveness, and purchase decisions. This type of research is a descriptive study with a quantitative approach with 100 respondents. The analytical tool used in this research is the EPIC Model method with SPSS software. The results of this study indicate that Bank BTN Youtube advertisements are proven to be effective. Furthermore, there is partially a positive and significant influence between empathy, persuasion, impact, and communication on purchasing decisions. Meanwhile, simultaneously the influence of empathy, persuasion, impact, and communication affect purchasing decisions.